Life Estimation of Knee Joint Prosthesis by Combined Effect of Fatigue and Wear. (2016) - Rawal, B.R.; Yadav, Amit; Pare, Vinod
Abstract: A total knee replacement (TKR) or total knee arthroplasty (TKA) is a surgery that replaces an arthritic knee joint with an artificial metal or plastic replacement parts called the 'prostheses'. The typical knee replacement, replaces the ends of the femur with metal femoral component and tibia with metal tibial component and plastic insert is inserted between them. During the walking cycle, knee joint prosthesis is subjected to cyclic loading which causes fatigue failure and sliding present between insert and femoral component enhances the wear process in plastic insert. In other words, the fatigue fracture and wear are basic mechanisms associated with knee joint prosthesis failure. In the previous failure analysis, fatigue and wear were separately analyzed. This paper estimates the life of Knee Prosthesis due to wear and fatigue individually as well as combined effect of both. Prosthetic material such as UHMWPE for insert & Ti6Al4 V, CoCrMo and 316L SS alloy for femoral and tibial component are chosen for analysis. To estimate wear, modified Archard's law is used, considering cross-shear motions responsible for wear. This wear results are used for estimation of prosthetic life. Fatigue phenomena is approached by using Finite Element Method (FEM) which gives life expectancy of knee prosthesis for various combination of materials and finally the combined effect of wear and fatigue is dealt that gives life expectancy of knee prosthesis.